A self-motives perspective on feedback-seeking behavior: Linking organizational behavior and social psychology research - ANSEEL, Frederick (Institutional Knowledge at Singapore Management University, 2007)
Both the feedback-seeking literature in management and the self-motives domain in social psychology have focused on how motives affect the way in which people acquire information for self-evaluation purposes. Despite apparent conceptual similarities, the implications of research in these domains have not been fully integrated. This paper aims to link research on feedback-seeking behavior to recent theoretical developments in social psychology. First, the current perspective in management on feedback-seeking motives is depicted. Second, a well-established framework of self-motives in social psychology is introduced. Third, similarities and differences between these two motivational perspectives are discussed and a first step towards integration is proposed. Fourth, it is demonstrated how a self-motives perspective might guide future research on six key issues. Self-motives might be useful in identifying new antecedents of feedback-seeking behavior, resolving inconsistencies in the feedback-seeking literature, understanding the interplay among feedback-seeking motives, integrating feedback-seeking and feedback reactions research, examining attitudinal outcomes of feedback-seeking motives, and enhancing the feedback-performance relationship.